Multi-omics analysis of SIV-specific CD8+ T cells in multiple anatomical sites. - Jennifer Simpson; Brittany Dulek; Paul Schaughency; Jason M Brenchley (PLoS Pathogens)
CD8+ T cells exert immunological pressure against immunodeficiency lentiviruses. In previous studies, we examined the TCR repertoire of CD8+ T cells specific for a single SIV immunodominant epitope, Gag-CM9, throughout SIV infection or after vaccination, and across multiple anatomic sites. We identified both tissue specific TCR sequences and TCRs shared by multiple anatomical sites. Here we use single cell RNA sequencing to evaluate if the tissue localization or TCR sequence of a CM9-specific CD8+ T cell corresponds with unique transcriptomics. CM9-specific CD8+ T cells were sorted from blood, lymph nodes, spleen, and liver from SIV infected rhesus macaques with progressive SIV infection and in animals who spontaneously control SIV replication after cessation of antiretroviral therapy. The cells were processed through a single cell sequencing protocol, creating a TCR amplified library and an RNA gene expression library corresponding to individual cells. Gene set enrichment analysis revealed no distinct transcriptional profiles for CM9 specific CD8+ T cells between different anatomical sites and between cells with shared or tissue specific TCRs. Similarly, no clear transcriptional profiles were associated with clonotypes which were shared across individual animals. However, CM9 specific CD8+ T cells from posttreatment controllers did exhibit enrichment of pathways associated with cellular activation compared to progressively infected animals, suggesting that altered transcription in distinct cellular pathways in antigen specific CD8+ T cells may associate with viral control. Together, these studies represent a thorough analysis of the relationship between anatomical and clonal origin, and the transcriptional profile of antigen specific CD8+ T cells and unravel pathways that may be important for CD8+ T cell mediated control of SIV replication.